Learning Preferences of Some Aboriginal and Torres Strait Islander Students in the Veterinary Program - Barnes, A.L. (The Australian Journal of Indigenous Education, 2000)
In 1989, a Professional Education Program for Aboriginal and Torres Strait Islander people (PEPA) was established at Murdoch University in Western Australia, to encourage the participation, retention and success of Indigenous Australians in studying for and qualifying as Veterinarians.